Person-centered care for dementia patients (frontend development) - Wong, Russell Kuan Hao (Nanyang Technological University, 2023)
Dementia is not a single ailment but rather a comprehensive term used to describe a spectrum of symptoms that individuals may encounter when dealing with various conditions, including Alzheimer's disease. These dementia symptoms trigger a decline in cognitive abilities substantial enough to impede daily functioning and self-sufficiency, impacting behavior, emotions, and interpersonal relationships.